A sclerosing stromal tumor of the ovary with masculinization in a premenarchal girl - Park, Soo Min; Kim, Young Nam; Woo, Young Jong; Choi, Ho Sun; Lee, Ji Shin; Heo, Suk Hee; Kim, Chan Jong (Clinical and experimental pediatrics, 2011)
A sclerosing stromal tumor of the ovary is an extremely rare benign tumor; it usually is found during the second and third decades of life. Patients present with pelvic pain or a palpable abdominal mass. Hormonal effects such as masculinization are uncommon. Here, an 11-year old premenarchal girl presented with deepening of the voice. In addition, clitoromegaly and hirsutism with a male suprapubic hair pattern were observed. The laboratory findings showed that the testosterone level was elevated to 3.67 ng/mL, andostenedione to above 10 ng/mL, dehydroepiandrosterone-sulfate to 346 µg/dL and 17-hydroxy progesterone (17-OHP) to 11.28 ng/mL. The chromosome evaluation revealed a 46,XX female karyotype. An adrenocorticotropic hormone stimulation test was performed. The 17-OHP to cortisol ratio in 30 minutes was 0.045, which suggested a heterozygote for the 21-hydroxylase deficiency. However, the CYP21A2 gene encoding steroid 21-hydroxylase showed normal. The pelvic ultrasound showed a heterogeneous mass consisting of predominantly solid tissue in the pelvic cavity. The pelvic magnetic resonance imaging revealed an 8.9×6.2×6.6 cm mass of the left ovary. A left oophrectomy was performed and microscopic examination confirmed a sclerosing stromal tumor. Immunohistochemical studies showed that the tumor was positive for smooth muscle actin and vimentin, but negative for S-100 protein and cytokeratin. Following surgery, the hormone levels returned to the normal range and the hirsutism resolved.